2016
DOI: 10.1038/ncomms11992
|View full text |Cite
|
Sign up to set email alerts
|

Prosaposin is a regulator of progranulin levels and oligomerization

Abstract: Progranulin (GRN) loss-of-function mutations leading to progranulin protein (PGRN) haploinsufficiency are prevalent genetic causes of frontotemporal dementia. Reports also indicated PGRN-mediated neuroprotection in models of Alzheimer's and Parkinson's disease; thus, increasing PGRN levels is a promising therapeutic for multiple disorders. To uncover novel PGRN regulators, we linked whole-genome sequence data from 920 individuals with plasma PGRN levels and identified the prosaposin (PSAP) locus as a new locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 63 publications
6
71
0
Order By: Relevance
“…Consistent with our study, PSAP was shown to regulate plasma PGRN levels in humans33. Thus, by forming a complex, PSAP and PGRN facilitate each other's lysosomal trafficking.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our study, PSAP was shown to regulate plasma PGRN levels in humans33. Thus, by forming a complex, PSAP and PGRN facilitate each other's lysosomal trafficking.…”
Section: Discussionsupporting
confidence: 90%
“…In fibroblasts which do not express sortilin, PGRN lysosomal trafficking is totally dependent on PSAP (Zhou et al 2015). The interaction between PGRN and PSAP was further confirmed by a large family-based genome-wide association study, in which polymorphisms in PSAP were shown to affect plasma PGRN levels (Nicholson et al 2016).…”
mentioning
confidence: 77%
“…The interaction between PGRN and PSAP was further confirmed by a large family‐based genome‐wide association study, in which polymorphisms in PSAP were shown to affect plasma PGRN levels (Nicholson et al . ).…”
mentioning
confidence: 97%
“…A homozygous loss-of-function mutation in the gene encoding prosaposin leads to a lysosomal storage disease known as sphingolipidoses, which is similar to NCL in that it results from failed lysosomal macromolecular degradation 54,58 . Thus, in some ways, it is not surprising that progranulin and prosaposin form heterodimers 59,60 and that prosaposin can regulate both intracellular and secreted progranulin levels 61 (FIG. 2).…”
Section: Trafficking Of Progranulinmentioning
confidence: 99%